To stay or not to stay intact as an allergen: the endolysosomal degradation assay used as tool to analyze protein immunogenicity and T cell epitopes - Öztemiz Topcu, Elif; Gadermaier, Gabriele (Frontiers in Allergy, 2024)
This review provides a comprehensive overview of allergenic molecules that have been analyzed by the endolysosomal degradation assay. The proteolytic susceptibility and degradation kinetics as well as the obtained peptides of the allergens are presented and related to their potential role in immunogenicity. We discuss the currently used endolysosomal degradation assay, provide information on relevant properties of the processed allergens, and give suggestions for methodological improvement and assay applicability.